Mandibular First Molar with Six Canals: Case Report of Radix Entomolaris and Middle Mesial Canal - Batista, Antonio; Lucato-Budziak, Maria; Michelotto, AndrÃ©; Xavier da Silva Neto, Ulisses (Iranian Endodontic Journal, 2021)
The purpose of this article is to report a successful endodontic treatment of a mandibular first molar with six canals; three root canals in the mesial root, two root canals in the distal root, and one radix entomolaris. The incidence of two anatomical variations presented in this report, middle mesial canal and radix entomolaris, is generally low. Knowledge of the internal anatomy of the root canals and their possible variations, and use of magnification, such as the operating microscope or loupes, can increase the chances of finding additional canals, contributing to the success of endodontic treatment.